2019
DOI: 10.21608/jppp.2019.53671
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Potential and Characterization of Plant Extracts against Fusarium fujikuroi on Rice

Abstract: Bakanae rice disease caused by fungus Fusarium fujikuroi Nirenberg (F. fujikuroi) and occurs in the most growing rice areas of the world. Transmission of this disease by soil and seed, so seed addressing by different material is useful to control bakanae disease. This study is focused on antifungal activity for some plant extracts i.e. Ammi visnaga (A. visnaga), Eucalyptus globulus (E. globulus), Artemisia judaica (A. judai) and Coriandrum sativum (C. sativum) on the linear growth of F. fujikuroi. Identificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Tumescence and distortion of fungal spores were found by using crude protein extract (Zhang et al, 2010 ). Additionally, extracts of plants such as Artemisia judaica, Eucalyptus globulus, Coriandrum sativum , and Ammi visnaga effectively reduced F. fujikuroi mycelial growth (Kalboush and Hassan, 2019 ). Essential oils extracted from Cinnamomum tamala (Baria and Rakholiya, 2020 ) , Eucalyptus citriodora (Gupta and Kumar, 2020 ), Cymbopogon martini (Akhila, 2009 ), and Mentha piperita (Habibi et al, 2018 ) were reported to have antifungal activity and effectively suppressed F. fujikuroi activity.…”
Section: Control Methodsmentioning
confidence: 99%
“…Tumescence and distortion of fungal spores were found by using crude protein extract (Zhang et al, 2010 ). Additionally, extracts of plants such as Artemisia judaica, Eucalyptus globulus, Coriandrum sativum , and Ammi visnaga effectively reduced F. fujikuroi mycelial growth (Kalboush and Hassan, 2019 ). Essential oils extracted from Cinnamomum tamala (Baria and Rakholiya, 2020 ) , Eucalyptus citriodora (Gupta and Kumar, 2020 ), Cymbopogon martini (Akhila, 2009 ), and Mentha piperita (Habibi et al, 2018 ) were reported to have antifungal activity and effectively suppressed F. fujikuroi activity.…”
Section: Control Methodsmentioning
confidence: 99%
“…Distortion and tumescence of germinated spores were observed following treatment with the crude protein extract [65]. Extracts of Eucalyptus globulus, Artemisia judaica, Ammi visnaga, and Coriandrum sativum decreased the growth of F. fujikuroi [77]. Baruah et al [78] demonstrated that essential oils of Eucalyptus citriodora, Cinnamomum tamala, Mentha piperita, and Cymbopogon martini var.…”
Section: Natural Productsmentioning
confidence: 99%